Cleaner production of antimicrobial and anti-UV cotton materials through dyeing with eucalyptus leaves extract - da Silva, Marcia Gomes (2018)
Nowadays, there is a growing interest in using natural substances to produce value-added and sustainable textile materials. Some plant extracts can simultaneously dye and impart new functionalities to textile fibers. In this context the main goal of the present study was the development of anti-UV and antimicrobial cotton fabrics through dyeing with aqueous extracts obtained from eucalyptus leaves. The extract was composed by several flavonoids, which were detected by high performance liquid chromatography and mass spectrometry (LC-ESI-MS/MS) and showed antimicrobial activity against Escherichia coli, Staphylococcus aureus and Candida albicans. The dyeing process was optimized considering the influence of its most important variables, such as temperature, pH and concentration of electrolytes. The influence of a pre-treatment with chitosan in the color strength was also evaluated. The best results were achieved with dyeing at 100 degrees C, pH 4.5 and adding 20 gL(-1) of NaCl to dyebath solution. However, the pretreatment with chitosan provided fabrics with increased color strength, better fastness properties and becomes the process more sustainable, since it eliminates the use of electrolytes. Dyed cotton fabrics showed antimicrobial activity against S. aureus and C. albicans, which increases with the extract concentration in the dyebath. The UV protection factor (UPF) of the dyed fabrics also showed a significant increase after the dyeing process. Additionally, the pre-treatment of cotton with chitosan increases antimicrobial activity and anti-UV protection of the dyed materials. (C) 2018 Elsevier Ltd. All rights reserved.